Heteroepitaxial Hexagonal (00.1) CuFeO2 Thin Film Grown on Cubic (001) SrTiO3 Substrate Through Translational and Rotational Domain Matching. Issue 6 (4th April 2021) - Luo, Sijun; Harrington, George F.; Wu, Kuan-Ting; Pergolesi, Daniele; Lippert, Thomas
Abstract : Heteroepitaxy of complex oxide thin films is a significant challenge when a large mismatch in the lattice parameters (>8%) and difference in the crystallographic symmetry coexist between the film and substrate. Herein, the heteroepitaxial growth of a hexagonal delafossite CuFeO2 thin film with (00.1) orientation on a cubic perovskite (001) SrTiO3 substrate through translational and rotational domain matching epitaxy is reported. The rotational in‐plane domain orientation relationships are CuFeO2 [11.0]//SrTiO3 [110] and CuFeO2 [2 1 ¯ .0]//SrTiO3 [110] with about 10% in‐plane lattice mismatch. The 14.8 nm‐thick (00.1) CuFeO2 thin film shows high‐crystalline quality with a full width at half maximum of rocking curve of about 0.24° and exhibits a possible indirect optical bandgap of 1.43 eV or direct optical bandgap of 1.94 eV. Herein, not only a model system demonstrating translational and rotational domain matching heteroepitaxy of complex oxides is reported, but also a way to thin‐film heterostructures integrating hexagonal delafossite with cubic perovskite materials for functional oxide devices is opened. Abstract : Heteroepitaxial hexagonal (00.1) CuFeO2 thin film grown on a cubic (001) SrTiO3 substrate through translational and rotational domain matching is demonstrated. New insights into the heteroepitaxial oxide systems with crystallographic symmetry dissimilarity and large lattice mismatch are provided.